The in fieri process of the effective integration of the principle of gender equality in the Court culture according 2030 Agenda for Sustainable Development - Melado Lirola, Ana Isabel (EUNOMÍA. Revista en Cultura de la Legalidad, 2023)
The trajectory towards gender equality is tortuous. The clarity of the rules and the forcefulness of the arguments, even more often than expected, are dismantled at the speed of a simple click when the jurists who know and work with real cases are unable to grasp the true meaning of legal norms and oppose resistance to the deployment of the legitimate rights and interests of women due to an erratic judicial culture that resists legal, economic and social evolution in accordance with the Law. The question to rethink then is, what is the reason for this gap between theory and reality that, moreover, legally does not occur in other legal fields?